Hasil Belajar Sejarah Siswa Dengan Media Pembelajaran Canvas Instructure Pada Kelas X Man 2 Banda Aceh - Nailis Sovia (Sociale : Journal of Social Science, 2026)
History learning outcomes remain a challenge in the learning process, partly due to the suboptimal use of learning media that can enhance student engagement. This study aims to examine the implementation of Canvas Instructure as a learning medium and students’ history learning outcomes in Class X-E1 at MAN 2 Banda Aceh. The study employed a quantitative approach using a pre-experimental design with a One-Shot Case Study. The sample consisted of 27 students. Data were collected through observation and a post-test, then analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a One-Sample t-Test. The results showed that the implementation of Canvas Instructure supported by the Blended Learning model obtained an observation score of 95%, categorized as very good. The students’ average learning outcome reached 84.17, exceeding the Minimum Mastery Criterion (KKM) of 80, with a learning mastery percentage of 75%. The hypothesis test showed a calculated t-value of 1.935 > the critical t-value of 1.714 at a 5% significance level, leading to the rejection of H₀ and acceptance of Hₐ. Therefore, Canvas Instructure supported by the Blended Learning model is effective in improving the history learning outcomes of Class X-E1 students at MAN 2 Banda Aceh.